Fe2o3 nanoparticle-based q-switched pulse fiber laser - Muhammad, Farah Diana; Liew, Josephine Liew Chyi; Mohd Asran, Anom Nazirah; Alresheedi, Mohammed Thamer; Eng, Khoon Ng; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2023)
We demonstrate the utilization of iron oxide (Fe2O3) as light-absorbing material in an erbium-doped fiber laser (EDFL) for the generation of Q-switched pulses. A sandwich-type saturable absorber (SA) with Fe2O3 nanoparticles between fiber ferrules is proposed. A fiber ferrule tip is tapped onto a cap of index-matching gel, which is then dipped into Fe2O3 nanoparticle powder to allow its deposition through the adhesion effect. By incorporating Fe2O3–SA in an EDFL, self-started and stable Q-switched pulses are attained at a threshold power of 50.1 mW. The pulse repetition rate is tunable from 9.92 kHz to 22.47 kHz, whereas the pulse duration reduces from 38.4 µs to 13.8 µs with the pump power increment. The maximum pulse energy achieved is 36.9 nJ. This work offers a simple integration method of Fe2O3 nanoparticles as potential SAs for the generation of Q-switched pulses.